2023
DOI: 10.1049/elp2.12292
|View full text |Cite
|
Sign up to set email alerts
|

Design and modelling of three‐to‐five phase three‐limbed transformer

Abstract: This study presents a design study and modelling of three‐to‐five phase transformer with three‐limb magnetic core. The basics of phase transformation windings are discussed. The purpose of such winding is to produce at the secondary a balanced multiphase voltage system, from multiphase primary of different number of phases, without unbalance in the primary and secondary under load conditions. In order to overcome the imbalance due to the dispositions of the winding coils on the magnetic core, simulations using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…By reviewing the relevant information of this transformer [15], it was found that both the initial values of the 24 state variables in Table 2…”
Section: Condition Evaluation System Of Transformermentioning
confidence: 99%
“…By reviewing the relevant information of this transformer [15], it was found that both the initial values of the 24 state variables in Table 2…”
Section: Condition Evaluation System Of Transformermentioning
confidence: 99%